GIG Economy sebagai Sumber Ekonomi Baru Penduduk Kelas Menengah di Jakarta - Arafat, La Ode Ahmad; Pratama, Siectio Dicko; Rahadiana, Rizal (UI Scholars Hub, 2025)
The weakening purchasing power of the middle class in Jakarta due to income stagnation and rising prices has encouraged the search for additional sources of income. The gig economy, which offers flexibility and higher income opportunities, is a potential alternative. This study aims to analyze the characteristics of middle-class workers and gig workers and measure the potential of the gig economy in increasing income. Analysis of the 2023 National Labor Force Survey (Sakernas) shows that 82.42% of Jakarta workers are middle class, the majority of whom have a high school education with an average income of 4.8 million rupiah per month. Meanwhile, gig workers with shorter working hours (44 hours/week) have an average income of 7 million rupiah. The results of the Propensity Score Matching (PSM) show the difference in income between gig and non-gig workers is 293,432 rupiah, increasing to 1,559,339 rupiah without the transportation sector. Logistic regression confirms that education, experience, and working hours have a significant effect on the opportunity to work in the gig economy. This finding emphasizes the importance of gig economy to potentially be the additional source of income for the middle-class workers, especially through skilled gig jobs. Therefore, the government needs to provide experience-based training (experiential learning) and promote the gig economy as a strategy to improve the welfare of middle-class in Jakarta.